Geochemical Characteristics of Expelled and Residual Oil from Artificial Thermal Maturation of an Early Permian Tasmanite Shale, Australia - Xiaomin Xie (MDPI AG, 2021)
Lipid biomarkers play an important role in defining oil-source rock correlations. A fundamental assumption is that composition (or ratios) of biomarkers in oil is not significantly different from that in bitumen in the source rock. In order to compare the geochemical characteristics of expelled oil and residual oil, a Permian Tasmanite oil shale was used for an artificial maturation experiment to simulate the oil generation period. The results show that the Tasmanite oil shale generated high amounts of hydrocarbons (731 mg HC/g TOC) at low maturation temperatures (340 °C). The hydrocarbon (HC) group compositions are different between the expelled oil (with more aromatic HC and saturated HC) and the residual oil (with more resin fraction and asphaltene). The Pr/Ph ratio (up to 4.01) of the expelled hydrocarbons was much higher than that in residual oil (<1.0). Maturity-related biomarkers Ts/(Ts + Tm), and αααC29-20S/(20S + 20R) and C29-αββ/(ααα + αββ), also showed complicated variations with pyrolysis temperature, especially at post peak oil generation. C27-, C28-, and C29- sterane distributions showed variations with pyrolysis temperature. Therefore, without considering the influence of maturity on the abundance of compounds, either source, maturity and/or organic matter type from the chemical characteristics may not be correct.